Bandwidth-Variable and Wavelength-Tunable Waveguide Bragg Grating Filter - Luyao Xie; Lawrence R. Chen (IEEE Photonics Journal)
We propose and demonstrate a waveguide Bragg grating filter that is bandwidth-variable and wavelength-tunable. The filter is implemented using a pair of apodized waveguide Bragg gratings in silicon-on-insulator that are tuned thermally. The bandwidth-variable functionally is achieved by tuning one of the two gratings while holding the other fixed; the corresponding 3 dB bandwidth of the passband can be varied from 2.28 nm to 7.39 nm. For the wavelength tunable filter, the center wavelength can be tuned from 1546.21 nm to 1549.57 nm while maintaining a passband bandwidth of 4.20 nm, or to be tuned from 1556.68 nm to 1562.56 nm while maintaining a passband bandwidth of 2.60 nm. A stopband response can also be wavelength tuned while conserving a 3 dB bandwidth of 5.70 nm. The wavelength tunability is achieved by tuning the two gratings simultaneously.